1998
DOI: 10.7589/0090-3558-34.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Serologic and Parasitologic Survey of the Endangered Attwater's Prairie Chicken

Abstract: Because conservation biologists have postulated that infectious diseases may have potentiated the endangerment of the Attwater's prairie chicken (Tympanuchus cupido attwateri), free-living prairie chickens were surveyed from all remaining populations for helminthic endoparasites and antibody against the etiological agents of nine infectious diseases. Samples from 4 of 27 adult males were positive for anti-Pasteurella multocida antibody. All other serologic tests were negative (n = 19). We identified Dispharynx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Parasite infection is one of the factors influencing population fluctuations of wild mammals and avians [1,3,8], and it should be noted that gastrointestinal parasites affect the red grouse (L. lagopus scoticus) population in Britain [2,5]. However, there are only a few studies on parasitic infections in the Japanese rock ptarmigan; including reports on blood parasites [4] and one of the intestinal coccidian parasites, Eimeria uekii, which was reported in 1981 [6].…”
mentioning
confidence: 99%
“…Parasite infection is one of the factors influencing population fluctuations of wild mammals and avians [1,3,8], and it should be noted that gastrointestinal parasites affect the red grouse (L. lagopus scoticus) population in Britain [2,5]. However, there are only a few studies on parasitic infections in the Japanese rock ptarmigan; including reports on blood parasites [4] and one of the intestinal coccidian parasites, Eimeria uekii, which was reported in 1981 [6].…”
mentioning
confidence: 99%
“…How easily avian cholera can be transmitted from waterfowl to other species, including prairie-chickens is not known . Peterson et al (1998) found T. cramae in eight of nine suitable samples from APC, representing the first report of this parasite in prairie grouse. Infected individuals, which came from all three remaining APC populations, had T. cramae infection intensities averaging 1,019.3, similar to that seen for T. tenuis in red grouse (Lagopus lagopus scoticus) .…”
Section: Survival and Mortality Factorsmentioning
confidence: 78%
“…Peterson (2004) also indicated Histomonas meleagridis (causative agent for blackhead), Pasteurella multocida (causative agent for avian cholera), E. dispersa, E. angusta, and other microparasites which result in high mortality have the potential to extirpate small, isolated prairie grouse populations. Peterson et al (1998) observed 4 of 27 (14.8%) APCs sampled were serologically positive for P. multocida antibodies. These four birds came from two of three remaining APC populations.…”
Section: Survival and Mortality Factorsmentioning
confidence: 84%
See 2 more Smart Citations